PERAN GURU PENDIDIKAN KEWARGANEGARAAN DALAM PENDIDIKAN KARAKTER PESERTA DIDIK KELAS X DI SMK NEGERI PAKU - Abdul Latief (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2016)
The research aims to know the role of teachers of Character Education Citizenship Education of Students of Class X in SMK Paku. This research is a descriptive study, the subjects of the research is students of Class X SMK Paku Polewali Mandar District of Binuang with 116 population Learners. The study sample consisted of 24 students with the data collection by using form observations, questionnaires, and interviews that are analyzed With way descriptive qualitative analysis using the formula fg Yang using frequency tables and will be analyzed with deductive, inductive, and comparative. The findings of research, find that the citizenship education teachers have the important role in learner character education. The teachers participation is formed character learners rated as the role of a teacher improve character learners, so the students can be recognized characters that it has, and find the character so that learners have the good mental and implement in everyday life. The teacher's role is very big to gave birth to man of character, because they are accountable hearts inculcate the positive nature is shown to the learners so that no arises deviations performed by learners due to moral decadence. master yang aware position as teachers will be more easy improve their students than teachers participants characters that just memposisiskan himself as lecturer.